3D-gedruckter Methanisierungsreaktor zur In-situ Co-Reformierung von Teeren bei der Methanisierung biogener Synthesegase - Müller, Jakob; Treiber, Peter; Karl, Jürgen (1. Jahrestreffen der Fachsektion Energie, Chemie und Klima (DECHEMA), 2024)

Adaptation of an additively manufactured reactor concept for catalytic methanation with in-situ tar co-reforming of biogenic syngas - Müller, Jakob; Feldner, Alexander; Markthaler, Simon; Treiber, Peter; Karl, Jürgen (Chemical Engineering Journal Advances, 2025)
Keywords: Tar removal; Heat pipes; Reactor design; Additive manufacturing; 3D-printing; Finite element analysis; Catalytic methanation

Allothermal gasification and integrated syngas cleaning by hot K2CO3 scrubbing for decentalized SNG production - Treiber, Peter (1. Deutsches Doktorandenkolloquium Biomasse (DBZF, 2018)

Allothermal gasification of biomass and lignite with integrated syngas cleaning for synthesis processes - Treiber, Peter; Schneider, Tanja; Neubert, Michael; Karl, Jürgen (Regatec 2017, 2017)

Allothermal Gasification of Lignite and Biomass with Integrated Syngas Cleaning and CO2 Removal - Treiber, Peter; Neubert, Michael; Karl, Jürgen (2016 AIChE Annual Meeting, 2016)

Allotherme Vergasung von Braunkohle und Gasreinigung mit integrierter Abtrennung von CO2 zur Optimierung des C/H/O-Verhältnisses im Produktgas - Treiber, Peter; Neubert, Michael; Leimert, Jonas; Karl, Jürgen (DGMK-Fachbereichstagung: Konversion von Biomassen und Kohlen, 2016)

CO2-Abscheidung in der Kalk-/Zementindustrie mit einer indirekt-beheizten Wirbelschichtkalzinierung unter 100% Wasserdampfatmosphäre - Böge, Kyra; Treiber, Peter; Karl, Jürgen (13. Österreichisches IEA Wirbelschichttreffen, 2023)

Combining the Heatpipe Reformer technology with hydrogen-intensified methanation for production of synthetic natural gas - Leimert, Jonas; Neubert, Michael; Treiber, Peter; Dillig, Marius; Karl, Jürgen (Applied Energy, 2018)

EU project CarbonNeutralLNG – Truly Carbon Neutral electricity enhanced Synthesis of Liquefied Natural Gas (LNG) from biomass - Treiber, Peter; Karl, Jürgen (Bio360 Expo 2024, 2024)

GreenLNG for mobility - The EU project CarbonNeutralLNG - Treiber, Peter; Karl, Jürgen (6th Nuremberg Workshop Methanation and 2nd Generation Fuels, 2023)

Influence of hydrocarbons and thiophene on catalytic fixed bed methanation - Neubert, Michael; Treiber, Peter; Krier, Claudia; Hackel, Marius; Hellriegel, Thomas; Dillig, Marius; Karl, Jürgen (Fuel, 2017)

Integrated Syngas Cleaning and CO2 Removal for Medium-scale Coal-to-SNG Plants - Treiber, Peter; Leimert, Jonas; Neubert, Michael; Karl, Jürgen (Synthesis Gas Chemistry - DGMK Conference, 2015)

Katalytische und biologische Direktmethanisierung von Biogas im Rahmen der Forschungsprojekte Power-to-Biogas, FlexBiomethane und IntenseMethane - Feldner, Alexander; Markthaler, Simon; Treiber, Peter; Karl, Jürgen (Statuskonferenz Bioenergie 2023, 2023)

Methanisierung im katalytischen Festbett für die SNG-Erzeugung in kleinen bis mittleren Anlagengrößen - Neubert, Michael; Treiber, Peter; Dillig, Marius; Karl, Jürgen (ProcessNet 2017, Jahrestreffen Fachgruppe Energieverfahrenstechnik, 2017)

Nachhaltige Prozesswärme: Konditionierung von biogenen Synthesegasen aus der Vergasung zur Nutzung in konventionellen Brennersystemen - Wondra, Christian; Treiber, Peter; Karl, Jürgen (31. Deutscher Flammentag, 2023)

Novel 3D-printed dual function methanation and in-situ tar co-reforming reactor - Müller, Jakob; Treiber, Peter; Karl, Jürgen (10th International Conference on Renewable Energy Gas Technology (REGATEC 2024), 2024)

Performance of a 100 kW Heatpipe Reformer operating on Lignite - Leimert, Jonas; Treiber, Peter; Neubert, Michael; Sieber, Aaron; Karl, Jürgen (Energy & Fuels, 2017)

Reactor Development for IHCaL Technology - Böge, Kyra; Treiber, Peter; Karl, Jürgen (ANICA – AC2OCem Workshop on Carbon Capture for the Cement and Lime Industry, 2023)

Self-sufficient hydrogen production from biogas by reformingand CO combustion - Feldner, Alexander; Treiber, Peter; Karl, Jürgen (75. Jahrestreffen der DECHEMA-Fachgruppe Hochtemperaturtechnik, 2023)

Simulation-Based Evaluation of a Two-Stage Small-Scale Methanation Unit for Decentralized Applications - Neubert, Michael; Widzgowski, Jonas; Rönsch, Stefan; Treiber, Peter; Dillig, Marius; Karl, Jürgen (Energy & Fuels, 2016)

Steam gasification of lignite and biomass with integrated syngas cleaning for decentralized SNG production - Treiber, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
The production of substitute natural gas from solid feedstocks involves thermochemical gasifica-tion, syngas cleaning, and catalytic methanation as key processes. Feedstocks as lignite or biomass are gasified with steam at temperatures above 800 °C and at a pressure of 5 bara or above. In contrast to other dual fluidized bed gasifiers, the Heatpipe Reformer technology can produce syngas at the ideal conditions for subsequent methanation. The pressurized synthesis gas is rich in hydrogen and essentially contains no nitrogen. However, the raw syngas has to undergo different cleaning steps before it can be fed to the methanation reactor to avoid catalyst poisoning. Aiming at decentralized small- to mid-scale plants, the applied gas cleaning technology has to be very effective while requiring as little investment costs as possible. Compared to large-scale cold methanol scrubbing, hot potassium carbonate scrubbing offers the required features as a suitable gas cleaning process. At last, optimization of the process combination can lead to an optimum operating point where high capital costs can be traded for minor catalyst consumption due to the bulk syngas cleaning capacity of the carbonate scrubbing process. Within the European research project CO2freeSNG2.0, this process chain is investigated in detail for the production of substitute natural gas from lignite. Considering the available literature, the Heatpipe Reformer is chosen as gasifying technology to be coupled with the Benfield process for syngas cleaning while methanation is performed with commercial nickel catalysts. Besides the pressurized steam gasification, the hot potassium car-bonate scrubbing is the key subject of this thesis. To evaluate the hot potassium carbonate scrubbing in a commercial size environment, a 50 MW lignite-to-SNG process chain is simulated under equilibrium conditions. Based on this simulation, the necessary mass and energy flows and the required removal efficiency for CO2 are defined. Also, a 100 kW rate-based simulation is set up for the dimensioning of the pre-pilot-scale syngas scrubbing unit at the Chair of Energy Process Engineering, Friedrich-Alexander-University Erlangen-Nürnberg. The experimental part of this thesis is performed at the bench scale and is based on syngas generation by a 5 kW pressurized fluidized bed steam gasifier. To be able to determine the influence of the syngas scrubbing, the gasification process is investigated with a focus on syngas quality and contaminants such as tars and sulfur components. Downstream the gasifier, a bench-scale syngas scrubber operating on a solution of 30 wt.-% potassium carbonate in water is added to the process line. The cleaned syngas is tested for gas composition and the scrubbing process is rated based on the removal efficiency of sour gases and the influence of the scrubbing process on other contaminants in the syngas. At last, the complete process chain is demonstrated on a 100 kW Heatpipe Reformer, a pre-pilot-scale Benfield scrubber, and a slipstream methanation reactor. The influence of wall and scale effects can, therefore, be minimized while the general results from the bench-scale tests are validated. The results prove the general capability of the hot carbonate scrubber as bulk sour gas removal and demonstrate the influence of process parameters in gasification and gas cleaning on the syngas quality.<br
Keywords: Vergasung; Biomasse; Braunkohle; Synthesegas; Benfield process; Carbonate scrubbing; Gasification; Syngas Cleaning

Steam methane reforming at low S/C ratios for power-to-gas applications - Großmann, Katharina; Treiber, Peter; Karl, Jürgen (International Journal of Hydrogen Energy, 2016)
Steam reforming is a well-established industrial process for the production of hydrogen from hydrocarbon fuels, in most cases from natural gas. High steam to carbon ratios are applied to gain maximum methane conversion. Since steam reforming of natural gas is a highly endothermic reaction it may also be applied as a chemical storage of renewable energy. For this power-to-hydrogen application milder conditions and shorter operating times are characteristic. However process efficiency declines with increasing S/C ratio for storage applications. Though, when lowering S/C ratios one of the major challenges lies in coke formation due to unwanted reactions. On this reason, experiments with different hydrocarbon feedstock, including methane and a synthetic natural gas mixture were conducted in a laboratory test rig to investigate the influence of very low S/C ratios in the range of 0.1e0.4 and reaction temperatures between 450 and 500 °C at atmospheric pressure. Measurements showed drastic decrease of catalyst life times when small amounts of ethane and propane were added to the hydrocarbon feedstock. Long-term tests showed that catalyst deactivation led to flattening of the temperature profile, changes in dry product gas composition and rising pressure drop over fixed bed. Increase of reaction temperature, lowering of S/C and use of higher hydrocarbons in the feed led to intense carbon lay down.
Keywords: Hydrogen; Heterogeneous catalyst; Steam reforming; Coke formation; S/C ratio; Power-to-gas

The Heatpipe Reformer with optimized combustor design for enhanced cold gas efficiency - Leimert, Jonas; Treiber, Peter; Karl, Jürgen (Fuel Processing Technology, 2016)
Keywords: Cold gas efficiency; Combustion; Emissions; Gasification; Heatpipe Reformer

The impact of tar contaminants on SOFC performance under high fuel utilization condition - Li, Yixing; Grimm, Fabian; Neubert, Michael; Treiber, Peter; Karl, Jürgen (Jahrestreffender ProcessNet-FachgruppeEnergieverfahrenstechnik, 2021)

Trickle-Bed Reactor For Biological Methanation - Weidlich, Tobias; Trabold, Thomas; Neubert, Michael; Treiber, Peter; Karl, Jürgen (BayWISS Jahreskolloquium 2019, 2019)

Trickle-Bed Reactor for Biological Methanation - Weidlich, Tobias; Trabold, Thomas; Neubert, Michael; Treiber, Peter; Karl, Jürgen (Proceedings of the ICPS 19, 2019)

Utilization of Synthetic Steel Gases in an Additively Manufactured Reactor for Catalytic Methanation - Hauser, Alexander; Feldner, Alexander; Treiber, Peter; Grimm, Fabian; Karl, Jürgen (Sustainability, 2023)
The path to European climate neutrality by 2050 will require comprehensive changes in all areas of life. For large industries such as steelworks, this results in the need for climate-friendly technologies. However, the age structure of existing steelworks makes transitional solutions such as carbon capture, utilization and storage (CCUS) necessary as short-term measures. Hence, a purposeful option is the integration of technical syntheses such as methanation into the overall process. This work summarizes hydrogen-intensified methanation experiments with synthetic steel gases in the novel additively manufactured reactor ‘ADDmeth1’. The studies include steady-state operating points at various reactor loads. Blast furnace gas (BFG), basic oxygen furnace gas (BOFG) and three mixtures of these two gases serve as carbon sources. The methanation achieved methane yields of 93.5% for BFG and 95.0% for BOFG in the one-stage once-through setup. The results suggest a kinetic limitation in the case of BFG methanation, while an equilibrium limitation is likely for BOFG. There is a smooth transition in all respects between the two extreme cases. The reaction channel inlet temperature (Formula presented.) showed a large influence on the reactor ignition behavior. By falling below the threshold value, a blow-off occurred during experimental operation. By means of a simulation model, practical operating maps were created which characterize permissible operating ranges for (Formula presented.) as a function of the gas composition and the reactor load.
CRIS-Team Scopus Importer:2023-05-26
Keywords: BFG; BOFG; by-product gas; catalytic methanation; ignition behavior; simulation; temperature profiles

Vorschlag einer katalytischen Methanisierung für kleinskalige dezentrale SNG Erzeugung - Neubert, Michael; Hauser, Alexander; Treiber, Peter; Karl, Jürgen (DGMK-Tagung Thermische Konversion - Schlüsselbaustein für zukünftige Energie und Rohstoffsysteme, 2019)